Physical-chemical evaluation of craft beer made with coffee (Research, Society and Development, 2023)
Beer is composed of water, malt, hops and yeast and may have optional ingredients of animal or vegetable origin, which are called brewing adjuncts, which, in addition to being a source of starch and/or sugars, can impart different aromas to the drink. Spices, such as coffee, are used to impart flavor and aroma to foods and beverages. Craft beer is usually produced on a small scale and caters to more demanding consumers due to its high sensory quality. The aim of this study was to elaborate and evaluate the physicochemical characteristics of craft beer with and without coffee. After being bottled, the beers were analyzed for soluble solids, pH, color, acidity, alcohol content, dry extract, bitterness and total phenols. The standard of quality and identity of the beer was achieved as planned, with the analytical results in line with other works in the literature. The study makes room for future work, suggesting that a sensory analysis be carried out to observe changes in taste and odor.